2017
DOI: 10.1177/1535370216685436
|View full text |Cite
|
Sign up to set email alerts
|

Soy protein isolate inhibits hepatic tumor promotion in mice fed a high-fat liquid diet

Abstract: The impact of dietary components on cancer is a topic of great interest for both the general public and the scientific community. Liver cancer is currently the second leading form of cancer deaths worldwide. Our study has addressed the effect of the protein source on hepatic tumor promotion in a mouse model reflecting aspects of non-alcoholic fatty liver disease (NAFLD). A high-fat liquid diet with casein as the protein source promotes hepatic injury and tumor promotion in diethylnitrosamine-treated mice. Repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Morphine can cause injuries to liver and renal tissues. [ 5 12 ] Oxidative stress is a factor greatly involved in the liver damage caused by drugs and toxins. The increased activity of liver enzymes in serum indicates hepatic damage, which leads to the reduced performance of liver cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphine can cause injuries to liver and renal tissues. [ 5 12 ] Oxidative stress is a factor greatly involved in the liver damage caused by drugs and toxins. The increased activity of liver enzymes in serum indicates hepatic damage, which leads to the reduced performance of liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Nowadays, according to the epidemiologic studies on the role of soybean in preventing some cancers as well as its effects on preventing cardiovascular diseases and diabetes, consumption of soy-containing food has found a special place in the diet of people. [ 5 ] Genistein, with molecular formula 4', 5, 7-trihydroxy-isoflavone, is the major isoflavone in soybean. [ 6 ] It is the isoflavone that has received the most attention due to its estrogenic, neuroprotective, antioxidant, anti-inflammatory, and anti-proliferative effects.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al31 reported that soy leaf extracts are effective at reducing proinflammatory cytokines levels in blood vessels, including TNF-α, IL-6, IL-1β, CCL2, vascular cell adhesion molecule 1, and intercellular adhesion molecule 1. Moreover, Mercer et al32 reported that soy protein isolates have inhibitory effects on high-fat diet-induced hepatoma proliferation in mice, by reducing IL-6 and TNF-α expression. Consistent with these previous studies, our results indicate that consumption of fermented soybeans is effective at preventing inflammation and increasing immune system function during senescence and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, soy supplementation restored the activity of antioxidant enzymes (glutathione peroxidase and superoxide dismutase), reduced lipid peroxidation and improved histological features of the liver injury [ 44 ]. Additionally, other studies have reported beneficial effects of soy proteins in improving hepatic steatosis and hepatocellular carcinoma (HCC) [ 45 , 46 ]. Specifically, soy protein supplementation significantly reduced hepatocyte fat accumulation and tumor growth in high fat diet (HFD)- diethyl nitrosamine (DEN) and ethanol fed mice.…”
Section: Methodsmentioning
confidence: 99%